EKSISTENSI UNDANG-UNDANG NOMOR 21 TAHUN 2001 TENTANG OTONOMI KHUSUS BAGI PROVINSI PAPUA (Existence of The Act Number 21/2001 On Special Authonomy of Papua Province) - Rooseno Rooseno (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2016)
There are 13 airports in Papua and West Papua provinces, its land was recorded in the Besluit van de Nederlands Nieuw Guenia Gouverneur Number 63 /1961, dated on February 22 ,however, it do not recognized by common law of Papuans because of having no transfer of right`s certificate`s on land and certificate of right`s disengagement on customary land. Therefore, customary law communities want to replace the loss turn into money, also require compensation increasing their livelihoods, education,jobs, and many more. Hence, it will be wise, if provincial government of Papua, House of Regional Representatives (DPRD), and Indonesia Government c.q. the Ministry of Transportation of Indonesia agree and compromise after damages assesment of the Act No. 2/2012 provisions to pay compensation in order to improve the living standards of indigenous peoples, education, jobs, and providing airport manager of Corporate Social Responsibility (CSR). Keywords: 13 airports land, conflict of customary law communities, the Ministry of Transportation ofIndonesia ABSTRAK Ada 13 Bandara yang terletak di provinsi Papua dan Provinsi Papua Barat tanah dimasukkan dalam Besluit van de Nederlands Nieuw Guenia Gouvernour nomor 63 tahun 1961 22 Februari 1961, tetapi itu tidak diakui oleh hukum masyarakat adat karena tidak ada transfer sertifikat hak atas tanah dan sertifikat pelepasan hak atas tanah adat. Jadi karena itu masyarakat hukum adat ingin mengganti kerugian dalam bentuk uang, juga memerlukan kompensasi yang meningkatkan mata pencaharian masyarakat adat,pendidikan, pekerjaan, dan banyak lagi. Oleh karena itu bijaksana jika pemerintah provinsi Papua, DPRP, dan pemerintah Republik Indonesia c. q Kementerian Perhubungan setuju dan dikompromikansetelah penilaian kerusakan dibawah ketentuan dari undang-undang 2/2012 - membayar ganti rugi,uang kompensasi untuk meningkatkan standar hidup masyarakat adat, pendidikan, pekerjaan, dan menyediakan manajer Bandara CSR (Corporate Social Responsibility) Komunitas hukum di tanah divan Besluit Belanda Nieuw Guenia Gouvernour nomor 63 tahun 1961 22 Februari 1961. Kata kunci: 13 Tanah Bandar Udara, konflik, masyarakat hukum adat, Departemen Perhubungan.